Clinical Evaluation of Significance of 25(Oh)D Levels in Patients with Organophosphorus Poisoning - Kishan Gupta Bal; Kumar Ranva Anil; Lal Meena Shyam; Kumar Sonkaria Rakesh; Gupta Jigyasa (International Journal of Nutrition, 2018)
Introduction: Organophosphate (OP) pesticide poisoning is a major challenging public-health problem in developing countries. Vitamin D deficiency is pandemic, yet it is the most under-diagnosed and under-treated nutritional deficiency in the world and it has been reported to be clinically correlated with psychiatric illness and manifestation of severe systemic inflammatory response syndrome like ARDS. Thus vitamin D deficiency may affect clinical course and outcome in cases of OPP. Aim: To evaluate status of 25 hydroxyvitamin D (25(OH)D) level in OP poisoning and its correlation with outcome of such patients. Materials and Methods: Serum 25(OH)D levels were measured at the time of hospitalization by electro-chemiluminescent Assay in 96 patients (76 male and 20 female) suffering from OP poisoning. Diagnosis of OP poisoning was made by history of poisoning including container of the poison brought by patient’s relative, clinical examination and measurement of serum butyrylcholinesterase activity. All patients were evaluated as per Performa and follow up till discharge. Results: Mean level of 25(OH)D in our cases was 24.57±9.91ng/ml and 66.7% had low levels of 25(OH)D. Our study shows linear relationship between 25(OH)D level and duration of hospital stay. All cases of OP poisoning who developed severe manifestations like ARDS, Intermediate syndrome (IMS) were having significant 25(OH)D deficiency. Our study also shows lower levels of 25(OH)D were associated with poor outcome (11.27±3.21vs 27.02±8.54, p<0.001). Conclusion: Vitamin D deficiency in OP poisoning is associated with longer hospital stay, more requirement of ventilator support and high prevalence of complication (ARDS and IMS) and poor outcome. Awareness of 25(OH)D level in patients with OP poisoning may be important to improve outcome.
Keywords: 25-hydroxyvitamin D